Lagring av ordbok över äldre finskt skriftspråk i strukturerad form - Palkki, Riita (Nordiske Studier i Leksikografi, 2001)
The Dictionary of Old Finnish (VKS, Vanhan kirjasuomen sanakirja) is written using a structural program, FrameMaker+SGML (SGML = Standard Generalized Markup Language). The program is used in Unix environment. A Frame document consists of parts called elements, which are hierarchically organized in fields according to the Document Type Definition (DTD). In one field there can be several parallel or subordinate fields. The basic structure of the articles in VKS is as follows: index word with its variants, word class code, definition, data from old dictionaries, examples with sourcecodes, list of compound words. When writing an article for the VKS, several windows are needed. The window "Elements" contains all the elements of the dictionary. The "Structure View" shows a graphic outline of the document’s structure. The Document window is used when writing the text. Other windows, "Terminal" and "Text Editor", which do not belong to the Frame program, are also available. The written text can also be viewed on the screen in SGML format. When finished, the dictionary can be used in research for example as a text corpus.